Where do wintering cormorants come from? Long‐term changes in the geographical origin of a migratory bird on a continental scale. Issue 4 (18th February 2018) - Frederiksen, Morten; Korner‐Nievergelt, Fränzi; Marion, Loïc; Bregnballe, Thomas
Abstract: Populations of migratory birds often mix to a considerable extent in their wintering areas. Knowledge about the composition of wintering populations is highly relevant to management, not least for species such as the great cormorant Phalacrocorax carbo sinensis, prone to conflicts with human interests. However, few studies have been able to estimate long‐term changes in winter population composition. We use 30 years of ringing and recovery data (1983–2013) from all major breeding populations of cormorants in continental Europe (except the Black Sea region) to estimate partitioning probabilities (i.e. the probabilities of moving to specific wintering areas) using a Bayesian capture–mark–recovery model. Combining these results with information on breeding numbers and reproductive output in a population model, we estimate the size and composition of wintering populations in Europe and North Africa. Partitioning probabilities showed some variation over time, but were similar for first‐winter and older birds. Cormorants from the western part of the breeding range tended to winter progressively further west over time. This may be a density‐dependent response to the recent growth of more easterly breeding populations. All wintering populations grew rapidly over the study period, and their composition showed pronounced changes. All wintering populations were composed of birds from many different breeding populations, but the proportion of cormorants of more easterly origin increased markedly over time in most wintering areas. Policy implications . Cormorant wintering populations in Europe consist of mixtures of birds of different breeding origins. These mixtures are also highly variable over time. These factors reduce the chances of successfully limiting conflicts in specific wintering areas through, for example, regulation of breeding numbers in one breeding area. The dynamic nature of cormorant winter populations means that conflicts are best addressed when and where the conflict occurs, or on the scale of the entire continental population. It is unlikely that the latter will be cost‐effective and politically realistic.